The Impact of Employee Competence and the Use of Information Technology on Financial Accountability - Mhicael Susanto (Yayasan Cinta Negara Indonesia, 2026)
Financial accountability is a key aspect of achieving transparent and responsible organizational governance. However, various challenges in financial management persist, stemming from low staff competence and the suboptimal use of information technology. This study aims to analyze the impact of staff competence and the use of information technology on financial accountability. The research method used is a quantitative method with a survey approach. Data were collected through the distribution of questionnaires to officials involved in financial management within public sector organizations. Data analysis employed multiple linear regression to test the influence of each independent variable on the dependent variable. The results indicate that staff competence has a positive and significant effect on financial accountability. Furthermore, the utilization of information technology was also found to have a positive and significant impact on improving the quality of financial accountability. Simultaneously, both variables contribute significantly to enhancing an organization’s financial accountability. Thus, improving staff competence supported by the optimal utilization of information technology can serve as an effective strategy to strengthen financial accountability and foster more transparent, effective, and accountable financial governance